Strategi Pemasaran Digital dalam Optimalisasi Manajemen dan Peningkatan Kualitas Pelayanan Klinik Gigi - Cloudya Panjaitan, Caesary; Juslily, Marta; Juliawati, Mita; Aqila Raini, Annisa; Shelly Melyda, Ananda; Farah Az Zahra, Elviena; Shafira Putri Prana, Indira; Shafa Saristi, Salsabila (Fakultas Kedokteran Gigi Universitas Trisakti, 2025)
Background: The rapid advancement of digital technology has significantly transformed management systems and marketing strategies in dental clinics. Social media serves as a strategic platform for building brand image, facilitating direct communication with patients, and delivering educational content that enhances trust and loyalty. Analytical tools such as SWOT and STP are widely used to develop effective marketing strategies, assess service quality, and adapt to market dynamics. Digital marketing has evolved beyond promotion to become a strategic approach for improving service quality and strengthening professional credibility. Objectives: To analyze research findings on the implementation of digital marketing in optimizing management and improving service quality in dental clinics. Methods: This study employed a literature review design. Articles were retrieved from Google Scholar, PubMed, and ScienceDirect databases. Results: Digital marketing positively influenced communication effectiveness, management efficiency, and patient loyalty. Social media and electronic word-of-mouth expanded promotional reach, strengthened clinic branding, and enhanced patient–clinic interaction. The integration of SWOT and STP models supported strategic decision-making aligned with market characteristics. Conclusion: Well-planned and sustainable digital marketing strategies are essential for enhancing competitiveness, service quality, and patient satisfaction in dental clinics in the digital era.